Photovoltaic Power Plant Feasibility Study Based on Indonesia’s Renewable Energy Tariffs: A Study of Nusa Penida Solar Power Plant - Prahastono, Iswan; Paradongan, Hendry Timotiyas; Aditya, Indra A.; Banjarnahor, Kevin M.; Sinisuka, Ngapuli Irmea (International Journal of Energy Economics and Policy, 2023)
This study conducts feasibility study on 3.5 MW photovoltaic (PV) power plant in Nusa Penida based on Indonesia’s existing renewable energy tariffs. Three scenarios were developed utilizing RETScreen software, according to the power plant specification. Base case scenario was developed to determine the feasibility of the PV power plant based on independent power producer perspective. PLN scenario was developed to determine the feasibility of the PV power plant based on Indonesia’s state-owned electricity company. Clean-energy scenario was developed to determine the feasibility of the PV power plant if there was a 20/tCO2 emission reduction incentive in Indonesia. The base case scenario results showed that the existing PV tariffs for PV power plant project was not sufficient to make the project financially viable based on the IPPs perspective. The PLN scenario results showed that the PV power plant project is very profitable based on PLN perspective due to high cost-savings. The clean-energy scenario results showed that 20/tCO2 emission reduction incentive was sufficient to make the PV power plant project financially viable based on the IPPs perspective. Based on those results, this study recommends emission-reduction incentives as a mean of attracting more investors. This study also recommends PLN to utilize more PV power plant, especially if the region have high generation cost as a means to lower Indonesia’s energy cost thus making energy more accessible for everyone.